Kajian Komparatif Aspek Hukum Layanan Pendanaan Bersama Dengan Donasi Online Dalam Sistem Penyelenggaraan Elektronik di Indonesia - Rafli, Muhammmad; Nurhilmiyah, Nurhilmiyah (Dinasti Research, 2024)
This study uses normative research methods to examine the comparative legal aspects between Donasi onlineservices and online donations in the context of Indonesia's electronic delivery system. Using this approach, this study investigates the comparison and regulations governing the two mediums, namely Donasi onlineservices and online donations. In the era of increasing globalization, businesses are no longer viewed as mere economic units, but as an integral part of the society in which they operate. In this context, studying the legal aspects of companies is becoming increasingly important to understand how they deal with legal complexities and their presence in society. This approach is expected to enable the investigation of the legal aspects of co-funding and online donation services to not only provide an in-depth understanding of the two enterprises individually, but also reveal the common patterns and challenges that enterprises face in the context of law and their presence in society.